Observational study of leprosy presenting with solitary skin lesion from a tertiary care hospital in South India - Angoori Gnaneshwar Rao; Aparna Karnam (Wolters Kluwer Medknow Publications, 2023)
Background: Leprosy presents with varied clinical morphology, and most often the morphological pattern and distribution of lesions denote a particular spectrum of leprosy; however, it may not be correct in all the cases which can lead to under treatment and dissemination of infection, particularly, in multibacillary leprosy presenting with single skin lesion. Objective: The objective of the study was to describe cases of leprosy presenting with solitary skin lesion and to establish the spectrum by slit-skin smear (SSS) and histopathological examination of skin biopsy. Materials and Methods: A prospective study involving thirty cases of leprosy presenting with single skin lesion to the department of dermatology of a tertiary care hospital spread over 2 years. Examination of skin lesion and nerves was carried out, and details were recorded. Routine hematological and biochemical investigations were done. SSS from the lesion, both ear lobes, right elbow, left middle finger, and right middle toe and lesional biopsy was done. Bacteriological index and morphological index were calculated in all cases, and the diagnosis was correlated by histopathology. Results: Of the thirty cases studied, twenty were males (66.7%) and ten (33.3%) were females with male-to-female ratio of 2:1. The most common age group afflicted was 21-40 years (70%). Hypopigmented patch was the most common presentation 19 (63.3%) in our study. The most common site of patch was forearm in 9 (30%). Of the thirty cases, 20 (66.7%) were diagnosed as borderline tuberculoid, 9 (30%) as tuberculoid tuberculosis, and 1 (3.3%) as indeterminate leprosy. Ulnar nerve was the most common nerve involved (80%). Ten patients (33.3%) were positive and twenty (66.7%) were negative for acid-fast bacilli on SSS examination. Out of the thirty clinically diagnosed leprosy cases, 19 (63.3%) showed positive histopathological correlation. Conclusions: The presentation of borderline lepromatous leprosy and lepromatous leprosy as single skin lesion reinforces the fact that certain aspects of the host cell-mediated response and pathophysiology of this disease are still not fully understood. It illustrates the importance of SSS and biopsy in these cases as such cases are undertreated.